STRENGTHENING OF RUSSIA INFLUENCE IN THE REGION OF EQUATORIAL AFRICA (Вісник: Міжнародні відносини, 2024)
The global policy support of Ukraine by the vast majority of international subject and unprecedented sanctions against the Russian Federation stimulate the Moscow to look for another allies among the countries of the global South.The article analyzes how Russian Federation works for strengthening it’s influence in Equatorial Africa on the cases of Cameroon and Democratic Republic of the Congo. The special role of informational influence and military-political instruments is demonstrated (using of mercenaries, arms trade and illegally extracted resources from the Central African Republic).
Keywords: Ukraine, Russian Federation, information influence, Cameroon, Democratic Republic of Congo